Should Anacardium humile St. Hil be used as an antiulcer agent? A scientific approach to the traditional knowledge - Luiz-Ferreira, Anderson; Cola-Miranda, Maira; Barbastefano, Victor; Hiruma-Lima, Clélia Akiko [UNESP]; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina (Elsevier B.V., 2008)
The crude methanolic extract (ME) obtained from the leaves of Anacardium humile was evaluated orally at doses of 250-500-1000 mg/kg on gastric lesion on ethanol and piroxicam induced gastric lesions in rodents. All the tested doses significantly inhibited gastric lesions by 56 to 100%. These results seems to support the traditional use of this species in the treatment of gastric diseases. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Anacardium humile; antiulcerogenic activity; gastric diseases